2004
DOI: 10.1021/es049161j
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Immobilization in Micropores of Drinking-Water Treatment Residuals:  Implications for Long-Term Stability

Abstract: Drinking-water treatment residuals (WTRs) can immobilize excess soil phosphorus (P), but little is known about the long-term P retention by WTRs. To evaluate the long-term P sorption characteristics of one Fe- and one Al-based WTR, physicochemical properties pertinent to time-dependency and hysteresis of P sorption were assessed. This study also investigated the P sorption mechanisms that could affect the long-term stability of sorbed P by WTRs. Phosphorus sorption kinetics by the WTRs exhibited a slow phase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
111
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(135 citation statements)
references
References 48 publications
22
111
2
Order By: Relevance
“…The present study demonstrated the effectiveness of WTRs in removing As(V) from a low Fe/Al hydroxide containing sandy soil under a varying set of soil solution chemistry. The Al-WTR-amended soil had a greater As(V) sorption capacity than that of Fe-WTR-amended soil, consistent with previous experiments (Makris et al 2004;Nagar et al 2010). For lowest As load (125 mg kg -1 ), no pH-dependent effect was observed on As(V) sorption by Al-or Fe-WTRamended soil at both application rates (25 and 50 g kg -1 ).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The present study demonstrated the effectiveness of WTRs in removing As(V) from a low Fe/Al hydroxide containing sandy soil under a varying set of soil solution chemistry. The Al-WTR-amended soil had a greater As(V) sorption capacity than that of Fe-WTR-amended soil, consistent with previous experiments (Makris et al 2004;Nagar et al 2010). For lowest As load (125 mg kg -1 ), no pH-dependent effect was observed on As(V) sorption by Al-or Fe-WTRamended soil at both application rates (25 and 50 g kg -1 ).…”
Section: Resultssupporting
confidence: 89%
“…Initial arsenic load was 125 mg kg -1 . Data are the mean of three replicates ± one standard deviation more pronounced compared to Al-WTR-amended soil due to comparatively smaller external and internal specific surface area of Fe-WTR for anion sorption (Makris et al 2004). Arsenic(V) sorption (at a 25 g kg -1 application rate of Fe WTR) decreased to 97, 84, and 60 % at pH 3 and As:P ratios of 1:1, 1:2, and 1:5, respectively, which further decreased to 76, 57, and 55 % after increasing the pH to 8, compared to the control (without P) treatment (Fig.…”
Section: Effect Of Competing Ligands On As(v) Sorption By Wtr-amendedmentioning
confidence: 99%
“…Our results suggest that Se(0) may possibly be entrained in WTR microsites to such a degree that it was kinetically difficult to oxidize. Entrainment and long-term stability has been shown to occur for phosphate trapped in WTR micropores [4]. Oxic adsorption of Se(IV) onto WTR followed by purging with compressed air for 28 days also shows no apparent change in Se speciation, Se-O and Se-Al shell bond distance and coordination number, further supporting the contention that Se(IV) microsite adsorption is aiding in retention and oxidation resistance.…”
Section: Experiments 2 Andmentioning
confidence: 73%
“…Water treatment residuals (WTRs), a waste product of drinking water treatment facilities, tend to have a mineral form similar to amorphous Al(OH) 3 when alum is utilized. Because of their amorphous nature, WTRs have a large surface area (up to 105 m 2 g À1 ) [4] and are highly reactive. They have the proven ability to adsorb tremendous quantities of P [5,6] and have been shown to adsorb other oxyanions such as As(V), As(III), and ClO À 4 [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…7 a), implying the slow P-adsorption process. Makris et al [24] opined that the slow P-adsorption process of drinking water treatment plant sludge might be explained by intraparticle phosphate diffusion in micropores.…”
Section: Adsorption Mechanisms 441 Ligand Exchangementioning
confidence: 99%